The most important challenges facing governors of accounts in Algeria- A study of a sample of external auditors in Setif state - nemdil, meriem; hadjar, mabrouka (Journal of Research in Finance and Accounting, 2022)
The objective of this study is to recognize the most important challenges that may face the governors of accounts. So we distribute a questionnaire to a sample of 40 governors of accounts in Setif state. Only 33 of them are valid for analysis. Some of the most important results of the study were the following: there is a set of challenges facing the governors of accounts in Algeria, some of them related to the laws which regulate the profession .others related to the authorities concerned with regulating the profession, and others related to clients (ie, economic institutions requesting audit assignments), and other challenges. The study presented a set of recommendations such as: an effort should be made to modify the rules of pursuing the profession in Algeria. Imposing strict control on the governors of accounts accomplishments. And educating the governors of accounts about the important of commitment to professional ethics. And should be more concentration on the quality of teaching accounting and auditing in the Algerian universities.